PENGARUH TATA KELOLA PERUSAHAAN, STRATEGI BISNIS, PERTUMBUHAN PENJUALAN, LEVERAGE, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK - Rr. Febriyanti Arya Kinasih; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2021)
Taxes are the largest source of income in the State of Indonesia. However, in practice the government's goal of increasing revenue in the tax sector is at odds with companies. Thus, the purpose of this study was to determine the effect of corporate governance, business strategy, sales growth, leverage, and profitability on tax avoidance. This research is an empirical research that uses quantitative methods. Sampling using purposive sampling technique in order to obtain a sample size of 173. The data source of this study was obtained from the annual financial statements of companies in the manufacturing sector. This study shows the results that business strategy, sales growth, leverage, and profitability affect tax avoidance. Meanwhile, corporate governance proxied by independent commissioners, institutional ownership, audit committee, and audit quality has no effect on tax avoidance.Keywords : Tax avoidance, corporate governance, business strategy, sales growth, leverage, and     profitability.